(untitled) (diségno, 2020)
The REAACH-ID symposium (Representation for Enhancement and management through Augmented reality and Artificial Intelligence: Cultural Heritage and Innovative Design), originally scheduled in Turin on 26 and 27 May 2020, took place in virtual form (13 and 14 October 2020), to which events are converting due to the known needs produced by the pandemic. The formulation was particularly effective and compatible with the topics covered, allowing more immediate transitions between the different forms of digital content presented by the speakers, without preventing the sharing of analysis and critical considerations (read more).